Informal educational institutions' teachers debriefing in improving the learning quality - Mahyudin Ritonga; Sobhan Sobhan; Kholidah Kholidah; Salamat Simbolon (Community Empowerment, 2022)
Teachers in the TPQ/TQA/MDA programs have a heterogeneous abilities; some have exceptional abilities, while others have insufficient abilities. As a consequence, the aim of this program is to provide debriefing for teachers who want to improve their learning management skills in TPQ/TQA and MDA. Training methods such as lecture and demonstration techniques are used to carry out the program. As a result, at the beginning of the activity there were 24% teachers with a high school education background and did not yet have good skills in the management of Al-Quran learning. However, following the demonstration, their abilities appeared to improve, both in terms of recitation knowledge and makharij al-huruf, as well as class management and learning technique selection.